2008
DOI: 10.1038/ejhg.2008.71
|View full text |Cite
|
Sign up to set email alerts
|

Position effect leading to haploinsufficiency in a mosaic ring chromosome 14 in a boy with autism

Abstract: We describe an individual with autism and a coloboma of the eye carrying a mosaicism for a ring chromosome consisting of an inverted duplication of proximal chromosome 14. Of interest, the ring formation was associated with silencing of the amisyn gene present in two copies on the ring chromosome and located at 300 kb from the breakpoint. This observation lends further support for a locus for autism on proximal chromosome 14. Moreover, this case suggests that position effects need to be taken into account, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Compared to patients with normal chromosome 13, there was a decrease in NBEA expression level in patients with a chromosome 13 deletion indicating that NBEA may be a new tumor suppressor gene for MM. Some other patients with del [13] show a very high NBEA expression [38,92]. Pharmacological inhibition of the Notch pathway prevents drug resistance and sensitizes the myeloma cells to chemotherapy [93].…”
Section: Involvement Of Nbea and Lrba In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to patients with normal chromosome 13, there was a decrease in NBEA expression level in patients with a chromosome 13 deletion indicating that NBEA may be a new tumor suppressor gene for MM. Some other patients with del [13] show a very high NBEA expression [38,92]. Pharmacological inhibition of the Notch pathway prevents drug resistance and sensitizes the myeloma cells to chemotherapy [93].…”
Section: Involvement Of Nbea and Lrba In Cancermentioning
confidence: 99%
“…The identified candidate regions also encompass too many genes to be able to identify the causal genes. In an alternative approach, candidate genes have been identified by mutation analysis or positional cloning of genes located at or in the neighborhood of a chromosomal breakpoint [3,4,[11][12][13][14]. Recently, genome-wide association studies have been performed resulting in a large number of potentially important novel candidate loci [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of candidate gene association studies is that they require pre-existing hypotheses about the involved neurobiological systems, and these are very limited in ASD [119]. Other research methods include studying subjects with ASD associated with a single gene disorder or with a unique chromosomal defect affecting only one gene [1,[26][27][28][29]. In these genetically relatively simple models, molecular biology has already thrown some light on pathways involved in autism [102].…”
Section: The Genetics Of Asdsmentioning
confidence: 99%
“…[55][56][57] As has been shown recently in patients with Williams-Beuren syndrome, deletions may influence expression levels of the adjacent, nondeleted genes. 58 Recently, Castermans et al 59 showed that the AMYSIN gene located at 300 kb from a breakpoint of a ring 14 became silenced and this may account for the autistic phenotype of the patient. These examples indicate that other mechanisms than mere gene copy number alteration, such as gene silencing, may be involved in determining clinical phenotypes and therefore should be taken into account during interpretation of results from array-based aneuploidy profiling.…”
Section: Position Effects Of Segmental Aneuploidymentioning
confidence: 99%